PENINGKATAN CITRA PROGRAM STUDI TEKNOLOGI LABORATORIUM MEDIK MELALUI WEBINAR PROFESI - Puji Astuti; Khoirul Rista Abidin; Puspa Amalia; Fadli Sukandiarsyah; Zahro Mufida (Politeknik 'Aisyiyah Pontianak, 2021)
Background: Medical Laboratory Technologist (ATLM) is one of the important types of health workers in Indonesia. However, it is less popular than other health professions such as doctor, nurse, and midwife. This low image causes student interest in pursuing education in the Medical Laboratory Technology study program to be relatively low. The webinar about ATLM’s profession for students is expected to improve the image of the TLM study program. Purpose: This community service aims to improve the image of the medical laboratory technology study program through profession webinars. Result: The results of this dedication show that profession webinars are quite popular for the public with up to 120 webinar participants, but this webinar cannot directly improve the image of the TLM study program, which is marked by the low number of students who become students in the TLM department at Politeknik Aisyiyah Pontianak (35%). Conclusion: Webinars are a promotional medium that is in great demand, but it has not been able to improve the image of the medical laboratory technology study program. Continuous efforts are needed to be able to improve the image of a study program or profession.